Pendampingan Teknik Unit Teaching Untuk Penguatan Pendidikan Karakter Berbasis Nilai-Nilai Aswaja Di Sd Al-Qur’an Roudhotul Tholibin Kota Metro - Irhamudin HASYIM AS'ARI; Hasyim As’ari Hasyim As’ari; Muhammad Irvan Islami Muhammad Irvan Islami (Akademi Kebidanan Tahirah Al Baeti Bulukumba, 2023)
Unit Teaching Technique is a teaching technique that provides opportunities for students to be active and teachers can recognize and master learning as a unit. With this learning technique builds student creativity in learning so that learning does not seem boring. So that character education learning is based on Aswaja values. There are 18 (eighteen) kinds of characters issued by the Ministry of Education. To shape the character of students must have teaching behavior that applies in the area. In this case, the majority of Indonesia adheres to ahlus sunnah wal jamaah. So Aswaja values ​​must be applied in schools. These values ​​are tasamuh, tawazun, taadul and amar ma'ruf nahi munkar. These five values ​​are not only possessed by madrasas with nahdliyin backgrounds, but schools which are under the auspices of the education office can apply this attitude in order to produce students who have moral values. This attitude can be practiced and carried out by students and teachers both in the learning process and outside of learning. In the service that is being carried out, this is creating character education based on aswaja values ​​for students through good unit teaching techniques. As the location of the dedication was carried out at the educational institution unit of the Roudhotul Tholibin Al-Qur'an Elementary School students in Metro City